Learning at SD Muhammadiyah 9 Tanggulangin during the Covid 19 Pandemic - Eva Roesmadayanti Putri; Muhlasin Amrullah (Proceedings of The ICECRS, 2021)
Before the pandemic, learning was done face-to-face, which was carried out for a week. Online learning activities are usually carried out to provide material to students and provide online assignments to students. The obstacle experienced by the teacher is that the material presented to students is not good, students are also difficult to understand the material. The Covid-19 pandemic has changed the order of people's lives, not only attacking the country of Indonesia but also hitting the world. The existence of Covid-19 has forced people to stop activities outside the home that should be carried out as on normal days. The public must maintain a safe distance or what is known as physical distancing, a situation in which people are quarantined and isolated in their respective homes, including in carrying out work so that each vulnerable individual will not be infected with the Covid-19 virus. This study uses descriptive qualitative research methods. A qualitative approach is a research process to understand social or human problems by analyzing words to create a complex and comprehensive picture, and reporting detailed views of information obtained from sources of information in a natural environment. The qualitative approach also aims to investigate, discover, describe, and explain the quality or features of social influence that cannot be explained, measured, or described through a quantitative approach.